2009
DOI: 10.1007/s11033-009-9474-x
|View full text |Cite
|
Sign up to set email alerts
|

In silico cloning and characterization of p8 homolog cDNA from common urchin (Paracentrotus lividus)

Abstract: The p8 protein is a transcription factor with a basic helix-loop-helix motif and a nuclear localization signal. In the present study, a common sea urchin (Paracentrotus lividus) homolog of p8 cDNA was cloned, sequenced and characterized. The full-length p8 cDNA consists of 896 bp and encodes 71 amino acids with a molecular mass of 8.238 kD. Homology alignments found that several phosphorylation sites and the most negative (Asp and Glu)/positive (Arg) propensities charged residues were well conserved between P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…However, given that p8-L1 and p8-L2 decline to relatively low levels compared to p8 during certain developmental stages, p8 may play a more critical role in embryogenesis than either p8-L1 or p8-L2. Similar results have also bee reported in sea urchin and mice [1,7,26,[30][31][32]. Further studies, such as loss-of-function or dominant-negative approaches, are needed further clarify the roles of these genes in zebrafish embryo development.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, given that p8-L1 and p8-L2 decline to relatively low levels compared to p8 during certain developmental stages, p8 may play a more critical role in embryogenesis than either p8-L1 or p8-L2. Similar results have also bee reported in sea urchin and mice [1,7,26,[30][31][32]. Further studies, such as loss-of-function or dominant-negative approaches, are needed further clarify the roles of these genes in zebrafish embryo development.…”
Section: Discussionsupporting
confidence: 78%
“…Homologs of the p8 gene have subsequently been cloned and sequenced in both humans and mice [2,3]. This gene is conserved in mammals such as mice and cattle [1,2,4], but also in a wide variety of other organisms including brine shrimp [5], fruit flies [6], sea urchins [7], amphioxus [8], frogs [9], Atlantic salmon [10] and zebrafish [11]. Human p8 (Hp8) encodes an 82 amino acid polypeptide, which contains a basic helix-loop-helix (bHLH) motif and a canonical bipartite nuclear-targeting signal (NLS) which promotes nuclear targeting.…”
Section: Introductionmentioning
confidence: 99%
“…In rat, p8 was detected mainly in liver, stomach and salivary gland [1]. Recently, it has been shown for p8 to have the strongest expression in intestine of common urchin [16]. Collectively, a relatively higher expression of the p8 mRNA seems to be associated with gut-related organs or tissues in these species.…”
Section: Discussionmentioning
confidence: 93%
“…The p8 cDNAs have been cloned from both vertebrates such as human [2], rat [1], mouse [5], frog [3], Atlantic salmon (GenBank accession number ACI66304), zebrafish (GenBank accession number BF717555) and invertebrates such as common urchin [16], shrimp [17] and fruit fly [18]. Human, frog and mouse p8 homologues are 82, 82 and 80-amino acid long, respectively, while it is only 69-amino acid long in fruit fly [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…It remained undetectable in peripheral blood leukocytes (Vasseur et al 1999a). In the common sea urchin, it was reported that p8 was shown to have the strongest expression in intestine (Wang et al 2009). Recently, in amphioxus, p8 was detected in muscle, gill, foregut including hepatic caecum, hindgut, ovary, testis, and notochord, with the highest expression in gut, gill, and ovary.…”
Section: Discussionmentioning
confidence: 99%